Indonesian small medium enterprises (SMEs) and perceptions on Halal food certification - Abdul, Mohani; Ismail, Hashanah; Mustapha, Mazlina; Kusuma, Hadri (Academic Journals, 2013)
This paper reports on a study of entrepreneurs of small medium enterprises (SMEs) in food business in Indonesia and their perception of the halal certification process as currently adopted by Indonesia. A total of 102 usable questionnaires were analysed using SPSS to search for the mean score for each of the information on Halal certification process (HFC 1 to HFC 3). HFC 1 was regarding their perceptions towards market share, market competitiveness and the Halal certification process. HFC 2 was regarding their views on the government support and monitoring, while HFC 3 was on their perceptions on information dissemination. The study found that respondents who have heard of halal hub, have the intention to applying Halal certification for their food products, while Halal certificate for their product(s), self done record keeping and attained a certain level of education have significant different responses towards the Halal certification process.